2000
DOI: 10.1002/(sici)1096-8628(20000228)90:5<369::aid-ajmg5>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial tandem duplication of 6p: A case with partial trisomy (6)(p12p21.3)

Abstract: A de novo interstitial tandem duplication of 6p12p21.3 was observed in a 7-month-old boy with growth retardation, psychomotor delay and craniofacial, brain, limb, and genital anomalies. Fluorescent in situ hybridization using a chromosome 6 paint probe demonstrated that the extra material belonged to chromosome 6. Although it has been suggested that 6p25 is the critical band involved in the expression of the phenotype of 6p duplication, comparison of the clinical findings of this case with those from the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
0
28
1
Order By: Relevance
“…It was reported that duplications of 6p regions (6p21.1 -p22.2 and 6p12 -p21.3), in which the human PTK7 gene (6p21.1) is located, were related with developmental disorders (Villa et al, 2000;Ng et al, 2001). Interestingly, symptoms of the disorders include the craniofacial abnormalities, the limbs and skeletal abnormalities, and mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that duplications of 6p regions (6p21.1 -p22.2 and 6p12 -p21.3), in which the human PTK7 gene (6p21.1) is located, were related with developmental disorders (Villa et al, 2000;Ng et al, 2001). Interestingly, symptoms of the disorders include the craniofacial abnormalities, the limbs and skeletal abnormalities, and mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 42 previously reported patients with partial trisomy 6p, 28 involved inheritance from a parental balanced translocation [Fryns et al, 1983;Katafuchi et al, 1992;Wauters et al, 1993;Nakajima et al, 1995;Song and Li, 1996;Rothlisberger et al, 1999], three from a pericentric inversion [Wauters et al, 1993], ten were de novo [Turleau et al, 1978;Muneer et al, 1984;Eden et al, 1985;Burd et al, 1988;Chaveau et al, 1988;Wauters et al, 1993;Rudnik-Schoneborn et al, 1996;Delatycki et al, 1999;Villa et al, 2000], and one was directly inherited from an unbalanced parent [Delatycki et al, 1999]. The proximal breakpoint varied from p11 to p25 [Lytle et al, 1986;Scarbrough et al, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…None of these cases were studied with molecular techniques, so it is difficult to know exactly which cases would include RUNX2. Villa et al 15 reported that partial trisomy 6p is characterized by failure to thrive, recurrent respiratory infections, growth and psychomotor retardation, abnormal sutures, high forehead, choanal atresia, and other minor dysmorphic features. Detailed reports of cranial sutures are not available for these cases.…”
Section: Discussionmentioning
confidence: 99%
“…There were no imaging studies taken to clearly define the morphology of the cranial sutures. 15 Of the remainder of reported cases, 16Y18 only one links multiple copies of 6p21 specifically with craniosynostosis. 19 We report a pediatric case with a 6p quadruplication resulting in 4 functional copies of RUNX2.…”
mentioning
confidence: 99%